1982
DOI: 10.1071/bi9820207
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Hypothalamic Dopaminergic Control of Prolactin Secretion in the Hyperprolactinaemic Rat

Abstract: The possibility that chronic hyperprolactinaemia results in loss of the ability of hypothalamic dopamine activity to inhibit prolactin secretion was studied in rats. Two degrees of hyperprolactinaemia (moderate and gross) were induced in the animals following the chronic administration of two different doses of oestradiol valerate. In rats with high chronic serum prolactin concentrations (approximately 20 times normal) there was a profound increase in prolactin secretion following inhibition of brain dopamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Numerous studies have shown that PRL and PRL-releasing drugs stimulate the release of DA into the hypophysial portal blood and that these sub stances stimulate turnover of tuberoinfundibular DA neu rons [2,7,14,16,34,36,46]. The stimulatory effect of estra diol on DA release may be the result of the elevation in serum PRL and the subsequent positive feedback of PRL on DA release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that PRL and PRL-releasing drugs stimulate the release of DA into the hypophysial portal blood and that these sub stances stimulate turnover of tuberoinfundibular DA neu rons [2,7,14,16,34,36,46]. The stimulatory effect of estra diol on DA release may be the result of the elevation in serum PRL and the subsequent positive feedback of PRL on DA release.…”
Section: Discussionmentioning
confidence: 99%
“…31], suggesting a pituitary site of action. High estrogen doses have also been shown to increase hypothalamic content of PRL-releasing factor activity [28], suppress tuberoinfundi bular dopaminergic activity [5,6,12,13,32] and structurally alter the hypothalamus [3,32], In contrast, other reports have shown enhanced hypothalamic dopaminergic activity in estrogen-treated animals [7,9,14,16,34,36]. The role of serotonin (5-HT) in estrogen-induced pituitary hyperplasia is even less clearly defined [4], Acute elevation of PRL by estrogen enhanced 5-HT neurotransmission in the medial…”
mentioning
confidence: 89%
“…The doses used were the same as are commonly used to inhibit tyrosine hydroxylase activity (Scapagnini et at. 1970;Lemmer and Berger 1978;Smythe et al 1982a).…”
Section: Drugsmentioning
confidence: 99%
“…The high accuracy of this technique and its simplicity has enabled assessment of neuronal activities of the brain monoamines in relation to concurrent pituitary hormone release in broad studies of neuroendocrine control mechanisms and these studies have resulted in previously unrecognized drug effects being revealed (Smythe et al 1982a(Smythe et al , 1982b(Smythe et al , 1982c(Smythe et al , 1983.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation